PERBEDAAN KAPASITAS FUNGSI PARU PEKERJA TAMBANG BATUBARA ANTARA SHIFT SIANG DAN MALAM - Nadia Bunga Kalistra; Qomariyatus Sholihah; Nurul Hidayah (Berkala Kedokteran, 2015)
The capacity of lung function (FEV1%) is the volume of air expelled in the first second. Impairment of lung function capacity coal miners can be caused by shift work. The study aimed to determine the difference in lung function capacity of coal miners between day shift and night shift. Research method used analytic observational cross-sectional approach. The sample was selected using purposive sampling technique based on the criteria of the Gay and Diehl. A total of 60 samples based on inclusion criteria consisted of 30 people day shift and 30 people night shift. Samples were asked to fill out a questionnaire and pulmonary function tests by means of spirometry BLT-08. Results showed that the capacity of normal lung function 15 (50%) of workers and abnormal lung function capacity 15 (50%) of coal miners afternoon shift. The capacity of normal lung function 6 (20%) of workers and abnormal lung function capacity 24 (80%) of coal miners night shift. Data were analyzed by Chi-square test with p = 0.015 (p <0.05) showed that there was difference in lung function capacity of coal miners between day shift and night shift at PT. Hasnur Riung Synergy Rantau Period July 2014. Keywords: lung function capacity, work shift, day shift, night shift, coal miner